“The logic of print is a logic of places and travel”. Interview with Roger Chartier (Anclajes, 2023)
In this brief interview, the French historian Roger Chartier (Lyon, 1945) covers a series of concepts related to three of the major areas to which he has devoted most of his academic work over the last four decades. The first deals with the figure of the author and in it a conceptual arc is authenticated that goes from new technologies applied to literary production and changes in authorial models to a return to the classics. The second axis focuses on the book as a support for texts and is an attempt to cover the different materialities of said object (physical, electronic or audiobook books). The third axis, in this case a single broad question, reflects the relationships between the historiographical and literary sciences, how they intersect, and ways to approach the historicity of texts.
Keywords: Book; Author; History; Literature; Edition